The hatred of all against all? Evidence from online community platforms in South Korea - Koo, Jeong Woo; Suh, Chan S.; Chung, Jin Won; Sohn, Kyung Ah; Han, Kyungsik (PLoS ONE, 2024)
Background Over several years of recent efforts to make sense and detect online hate speech, we still know relatively little about how hateful expressions enter online platforms and whether there are patterns and features characterizing the corpus of hateful speech. Objective In this research, we introduce a new conceptual framework suitable for better capturing the overall scope and dynamics of the current forms of online hateful speech. Methods We adopt several Python-based crawlers to collect a comprehensive data set covering a variety of subjects from a multiplicity of online communities in South Korea. We apply the notions of marginalization and polarization in identifying patterns and dynamics of online hateful speech. Results Our analyses suggest that polarization driven by political orientation and age difference predominates in the hateful speech in most communities, while marginalization of social minority groups is also salient in other communities. Furthermore, we identify a temporal shift in the trends of online hate from gender to age based, reflecting the changing sociopolitical conditions within the polarization dynamics in South Korea. Conclusion By expanding our understanding of how hatred shifts and evolves in online communities, our study provides theoretical and practical implications for both researchers and policymakers.
Keywords: Adult; Female; Humans; Internet; Male; Middle Aged; Politics; Republic of Korea; Young Adult